2023
DOI: 10.1002/app.53774
|View full text |Cite
|
Sign up to set email alerts
|

Flammability and vibrational study of graphene incorporated epoxy/ramie/glass hybrid nanocomposite

Abstract: Hybrid polymer composites are vastly used in aerospace, construction, and automotive fields. This study aims to analyze the flammability and vibrational behavior of graphene incorporated epoxy/ramie/glass (ERG) hybrid nanocomposite. The samples were prepared with different weight percentage of graphene (GR) through hand layup method, followed by vacuum bag technique. The samples were analyzed for water intake, porosity, mechanical strength, fractography, vibrational property together with flammability of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…It can be seen from Figure 9 that the improvements in tensile strength and elastic modulus reached a plateau at 2 wt% CNT concentration at different milling times. Thiyagu et al reported that an optimal limit is required due to the different physical properties of the polymer matrix and nanomaterials in their different studies 75,76 . This situation was attributed to the reinforcing effect of CNTs, which could act as load bearing and resisted deformation and fracture of the composite material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen from Figure 9 that the improvements in tensile strength and elastic modulus reached a plateau at 2 wt% CNT concentration at different milling times. Thiyagu et al reported that an optimal limit is required due to the different physical properties of the polymer matrix and nanomaterials in their different studies 75,76 . This situation was attributed to the reinforcing effect of CNTs, which could act as load bearing and resisted deformation and fracture of the composite material.…”
Section: Resultsmentioning
confidence: 99%
“…Thiyagu et al reported that an optimal limit is required due to the different physical properties of the polymer matrix and nanomaterials in their different studies. 75,76 This situation was attributed to the reinforcing effect of CNTs, which could act as load bearing and resisted deformation and fracture of the composite material. In this context, mechanical properties initially enhanced as the CNT content increased in the nanocomposite.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…NF is gaining more attention than SF due to being eco‐friendly, lightweight, inexpensive, easily handled, biodegradable, high in specific properties, nonabrasive, highly filled, low in energy consumption, skin‐friendly, carbon dioxide reducing, stiff and insulating, flexible and damping, low in density and available in a vast array of fiber categories 12,13 . Compared with other NF composites, the composite made of ramie fiber and epoxy has shown promising outcomes in producing automotive parts, ballistic applications, and door panels 14,15 . The fiber from ramie comprises 68%–76% of cellulose, 13%–16% of hemicellulose, 5% of ash, 1.9% of pectin, and 0.3% of wax 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins, being one of the significant thermosetting materials, holds a crucial position in various industrial sectors including construction, microelectronics, aerospace, and more 1–4 . This is primarily due to its outstanding adhesive and mechanical properties, remarkable chemical resistance, and superior insulation performance 5–11 . However, the highly flammable nature of epoxy resins during its application process presents a significant safety concern, thereby greatly restricting its usage 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This is primarily due to its outstanding adhesive and mechanical properties, remarkable chemical resistance, and superior insulation performance. [5][6][7][8][9][10][11] However, the highly flammable nature of epoxy resins during its application process presents a significant safety concern, thereby greatly restricting its usage. [12][13][14] Consequently, the flame-retardant modification of epoxy resins becomes particularly imperative.…”
Section: Introductionmentioning
confidence: 99%